EVALUATION OF THYROID HORMONE CHANGES DURING PREGNANCY - MALHOTRA, PREETI; TANWAR, KAVITA; CHITTARA, DIKSHA KUMARI; SOGANI, SONAL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Knowing the ideal levels of triiodothyronine (T3), thyroxine (T4), FT3, FT4, and thyrotropin-stimulating hormone (TSH) for each pregnancy trimester are the goal. Methods: The Department of Obstetrics and Gynecology at the Pacific Institute of Medical Sciences in Udaipur treated 150 patients (obstetric cases) for the current longitudinal research. The following parameters were examined for in a fasting blood sample: T3, T4, FT3, FT4, and TSH. Results: As a result, thyroid profile readings in every group (I, II, and III trimester) were increased and were maximum in second group or second trimester followed by third. The levels above the normal range were in 39 (12+12+15) women of all the groups. Conclusion: The second trimester of pregnancy saw the greatest increase in thyroid hormones readings. Thyroid profile was lower during the first trimester, particularly at par during the second, and decreased in third trimester.